Ability of Azathiacyclen Ligands To Stop Cu(Aβ)‐Induced Production of Reactive Oxygen Species: [3N1S] Is the Right Donor Set. Issue 14 (26th January 2023) - Malikidogo, Kyangwi P.; Drommi, Marielle; Atrián‐Blasco, Elena; Hormann, Jan; Kulak, Nora; Esmieu, Charlène; Hureau, Christelle
Abstract: Alzheimer's disease (AD) is an incurable neurodegenerative disease that leads to the progressive and irreversible loss of mental functions. The amyloid beta (Aβ) peptide involved in the disease is responsible for the production of damaging reactive oxygen species (ROS) when bound to Cu ions. A therapeutic approach that consists of removing Cu ions from Aβ to alter this deleterious interaction is currently being developed. In this context, we report the ability of five different 12‐membered thiaazacyclen ligands to capture Cu from Aβ and to redox silence it. We propose that the presence of a sole sulfur atom in the ligand increases the rate of Cu capture and removal from Aβ, while the kinetic aspect of the chelation was an issue encountered with the 4N parent ligand. The best ligand for removing Cu from Aβ and inhibiting the associated ROS production is the 1‐thia‐4, 7, 10‐triazacyclododecane [3N1S]. Indeed the replacement of more N by S atoms makes the corresponding Cu complexes easier to reduce and thus able to produce ROS on their own. In addition, the ligand with three sulfur atoms has a weaker affinity for Cu II than Aβ, and is thus unable to remove Cu from CuAβ. Abstract : Speedy silencer : Five 12‐membered macrocycles ranging from the [4N] to the [1N3S] binding set were challenged for their ability to stop and prevent the formation of reactive oxygen species induced by the Cu(Aβ) complex, where Aβ is the Alzheimer‐related peptide. The most appropriate ligand was [3N1S], which combines redox silencing of the copper ion with the speed of Cu removal from Aβ.